Avaliação técnico-econômica da produção de enzimas celulolíticas por fermentação em estado sólido - Mendes, Fabrício Bruno [UNESP] (2015)
This study evaluated different scenarios of cellulases production throw the conception of an industrial plant integrated with sugarmill unit which is able to produce second generation ethanol. For that, it is considerate sugarcane bagasse and wheat bran as substrates on the 7:3 proportion, 75% moisture content, fungi thermophilic Myceliophtora I1D3, 45ºC and 96h of fermentation process. Technical and economic evaluation were performed according to different sugarcane bagasse availability. The main economic indicators of this project (payback, net present value-NPV, return on investment-ROI and rate return intern-IRR) were evaluated and the results indicated the feasibility of this biotechnological process. However, indicators such as IRR and ROI had values below those normally accepted by investors of the sugarcane industry. The sensibility analysis also indicated the enzymatic activity an important factor of rentability of this project. Considering the scenario presented here and the alternative of increasing electricity cogeneration bagasse surplus, the production of cellulases by solid state fermentation still presented as more competitive alternative